2023
DOI: 10.1007/s00330-023-09725-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the OSASH score to predict overall survival of hepatocellular carcinoma after surgical resection: a dual-institutional study

Abstract: Objective To develop and validate a risk score based on preoperative clinical-radiological parameters for predicting overall survival (OS) in patients undergoing surgical resection for hepatocellular carcinoma (HCC). Methods From July 2010 to December 2021, consecutive patients with surgically-proven HCC who underwent preoperative contrast-enhanced MRI were retrospectively enrolled. A preoperative OS risk score was constructed in the training cohort using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In contrast to previous studies in HCC populations, 23,37 we did not identify high AFP levels as an independent predictor of MVI and recurrence in patients with LR-5 HCC, which is similar to recent study for LR-5 HCC patients. 39 The potential reason for the discrepancies among these studies may include selection bias in the study population or differences in sample size.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…In contrast to previous studies in HCC populations, 23,37 we did not identify high AFP levels as an independent predictor of MVI and recurrence in patients with LR-5 HCC, which is similar to recent study for LR-5 HCC patients. 39 The potential reason for the discrepancies among these studies may include selection bias in the study population or differences in sample size.…”
supporting
confidence: 59%
“… 35 This may reflect histological differences and tumor heterogeneity, explaining why the presence of mosaic structures serves as a risk factor for poor prognosis in HCC treatment. Previous studies have established mosaic architecture as a risk factor for TACE 23 , 36 and postoperative 17 , 37 , 38 recurrence in HCC patients. In agreement with these findings, our study also observed that HCC patients with mosaic structures had worse postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IA as a predictive biomarker has several advantages: CT or MRI is routinely performed preoperatively; IA can be easily recognized by distinguishing discrete arteries within the tumor and the interobserver agreement is good or excellent 32 , 33 ; IA is a prevalent feature presented in 28.9–52.3% of HCC 32 , 34 , 35 . Thus, a large proportion of HCC patients may benefit from using IA as a selection criterion.…”
Section: Discussionmentioning
confidence: 99%
“…On a per-lesion basis, the following features were evaluated: (a) tumor size (cm), (b) enhancement pattern (typical vs atypical, with typical enhancement pattern referring to the presence of non-rim APHE coupled with nonperipheral “washout” [ 19 ]), (c) rim APHE, (d) corona enhancement, (e) nonsmooth tumor margin, (f) incomplete tumor “capsule,” (g) delayed central enhancement, (h) enhancing “capsule,” (i) intratumoral necrosis, (j) fat in mass, more than adjacent liver, (k) radiological cirrhosis, (l) diffuse fatty change, (m) diffuse iron overload, (n) splenomegaly, (o) ascites, (p) collateral circulation, (q) gastroesophageal varices, and (r) main portal vein diameter (cm). Definitions of the imaging features haven been described in our prior study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%